Peningkatan Kualitas Sumber Daya Manusia Dalam Rangka Optimalisasi Pengelolaan Keuangan Desa Menuju Desa Berdikari (Studi Kasus di Desa Purwodadi Kecamatan Tegalrejo Kabupaten Magelang) - Shinta Ratnawati; Hanung Eka Atmaja; Dian Marlina Verawati (UNSIKA (Universitas Singaperbangsa Karawang), 2018)
This research will aim to improve the quality of human resources in Purwodadi Village, Tegalrejo Subdistrict, Magelang District in managing village finances. Supported by human resources who are able to work appropriately and efficiently, it can be ascertained that the steps of Purwodadi village to become a Berdikari Village are not impossible. The selection of Purwodadi village as an object in this study because in addition to the village has good natural potential, it is also supported by the village apparatus that has the desire to progress amid all the limitations in the village. To support this phenomenon, research will be carried out through the analysis of S.W.O.T-A.H.P. Through the analysis of S.W.O.T there will be a strategy formulation by combining internal factor (Strength and Weakness) with external factor (Opportunity and Threat). Then proceed with Analytic Hierarchy Process (A.H.P); A.H.P is one of the tools in decision making, this method is so powerful that it can be applied even in important decision making. This is because in A.H.P a priority is composed of various criteria that have been decomposed beforehand so that priority setting is based on a hierarchical process and makes sense. Specifically this study aims to: (1). identify indicators relating to human resources in village financial governance; (2). analyze S.W.O.T by using indicators in point (1); (3). through A.H.P a strategic decision will be made that will be used in improving human resources in village financial governance. The contribution of this research is to formulate a strategy to improve the quality of human resources is expected to bring the Village Purwodadi Tegalrejo District Magelang District towards the Self-Reliance Village. The output target of this study is the creation of human resource strategies in the management of village financial management towards self-sufficient villages, publications in national journals, speakers at national seminars and the creation of draft teaching materials.